Recent advances in photothermal materials for solar-driven crude oil adsorption - Li Jinyang; Wang Zhenyu; Deng Hanpeng; Li Jiayang; Wang Bin; Zhou Zuowan (Nanotechnology Reviews, 2022)
In recent years, the adsorption method is usually adopted in the actual treatment of crude oil spills. However, the high viscosity of crude oils prevents them from diffusing into the internal pores of the adsorbent, resulting in ineffective oil capture. Photothermal materials can reduce the viscosity of crude oil by in situ heating through the photothermal conversion effect, making it easier for crude oil to occupy the internal pores of the adsorbent. At present, the review of the application of photothermal materials in the field of crude oil adsorption is still blank. This review focuses on the application of novel photothermal conversion materials in the field of crude oil adsorption and their performance comparison. Among the photothermal conversion materials used in the field of crude oil adsorption, some are commercial sponges with high porosity and photothermal coating, while others are self-assembled three-dimensional porous structures of materials with inherent photothermal properties. This review mainly introduces the types and research progress of materials with good photothermal effect at home and abroad in recent years and summarizes some new research ideas and materials that can be applied to photothermal conversion.